River of smoke [compact disc, unanbridged] - Ghosh, Amitav. 1956- (Brilliance Audio, 2011)
The Ibis, loaded with a cargo of indentured servants, is in the grip of a cyclone in the Bay of Bengal. The storm also threatens the clipper ship Anahita, groaning with a large consignment of opium. And the Redruth, a nursery ship, carries Fitcher Penrose, a horticulturist determined to track down the priceless treasures of China that are hidden in plain sight. All will converge in Canton's Fanqui-Town, a powder keg awaiting a spark to ignite the Opium Wars.